Maize/legume rotation in Conservation Agriculture systems: IPSR Innovation Profile - Thierfelder, Christian L. (CGIAR System Organization, 2022)
Maize-legume rotations are traditionally practiced in areas where pest pressure is high and where soil fertility is limiting. Instead of growing just one crop (such as maize) in monoculture, the cereals are rotated with leguminous (cowpea, groundnuts, soybeans, common beans) or non-leguminous crops (sunflower, cotton etc.) on an annual basis. As a good agriculture practice, this is essential for all farming, particularly in Conservation Agriculture systems.